Building an e-commerce ecosystem for MSMEs in Medan: a strategic approach to design and user satisfaction - Gaol, Lasando Lumban (Enrichment : Journal of Management, 2024)
This study presents the design and evaluation of an e-commerce application tailored for Small and Medium Enterprises (SMEs) in Medan. Utilizing a Research and Development (R&D) approach and the system development life cycle (SDLC) model, the research identifies user needs and designs a solution to meet these needs. The solution includes features such as marketplace learning materials, a discussion forum, and marketplace recommendations. The design process involved creating storyboards, information architecture, wireframes, and mockups. The application's user experience was evaluated using the User Experience Questionnaire (UEQ), revealing a generally positive user experience with areas for improvement in efficiency. The research underscores the importance of such applications for the growth of SMEs and suggests further research to enhance user efficiency